KANDUNGAN UNSUR HARA TANAH DAN TANAMAN SELADA PADA TANAH BEKAS TSUNAMI AKIBAT PEMBERIAN PUPUK ORGANIK DAN ANORGANIK - Erida Nurahmi (Jurnal Floratek, 2010)
Various forms of soil damage can be seen from the changes in physical properties, chemical and biological soil which happens in almost all coastal areas affected by the tsunami. The objectives of the study were to investigate the influence of organic and inorganic fertilizers in tsunami-affected lands on the growth of lettuce, and elemental content of N, P, and K in soil and plants. Experiment was carried out in polybags. Result showed that organic and inorganic fertilizer increased nutrient status of N and P soil, increased growth and nutrient content of N and P in lettuce plants. While for nutrient content of K, organic and inorganic fertilizer only affected soil and roots of lettuce. Growth and nutrient content of N, P and K in soil and plants due to organic and inorganic fertilizer application was highly dependent on the dosage given. The best growth of lettuce was obtained at combination of organic fertilizer 30 tons/ha with inorganic NPK fertilizer 1000 kg/ha